Barriers and Facilitators to the Implementation of Digital Health Services for People With Musculoskeletal Conditions in the Primary Health Care Setting: Systematic Review - Mark Leendert van Tilburg; Ivar Spin; Martijn F Pisters; J Bart Staal; Raymond WJG Ostelo; Miriam van der Velde; Cindy Veenhof; Corelien JJ Kloek (JMIR Publications, 2024)
BackgroundIn recent years, the effectiveness and cost-effectiveness of digital health services for people with musculoskeletal conditions have increasingly been studied and show potential. Despite the potential of digital health services, their use in primary care is lagging. A thorough implementation is needed, including the development of implementation strategies that potentially improve the use of digital health services in primary care. The first step in designing implementation strategies that fit the local context is to gain insight into determinants that influence implementation for patients and health care professionals. Until now, no systematic overview has existed of barriers and facilitators influencing the implementation of digital health services for people with musculoskeletal conditions in the primary health care setting. ObjectiveThis systematic literature review aims to identify barriers and facilitators to the implementation of digital health services for people with musculoskeletal conditions in the primary health care setting. MethodsPubMed, Embase, and CINAHL were searched for eligible qualitative and mixed methods studies up to March 2024. Methodological quality of the qualitative component of the included studies was assessed with the Mixed Methods Appraisal Tool. A framework synthesis of barriers and facilitators to implementation was conducted using the Consolidated Framework for Implementation Research (CFIR). All identified CFIR constructs were given a reliability rating (high, medium, or low) to assess the consistency of reporting across each construct. ResultsOverall, 35 studies were included in the qualitative synthesis. Methodological quality was high in 34 studies and medium in 1 study. Barriers (-) of and facilitators (+) to implementation were identified in all 5 CFIR domains: "digital health characteristics" (ie, commercial neutral [+], privacy and safety [-], specificity [+], and good usability [+]), "outer setting" (ie, acceptance by stakeholders [+], lack of health care guidelines [-], and external financial incentives [-]), "inner setting" (ie, change of treatment routines [+ and -], information incongruence (-), and support from colleagues [+]), "characteristics of the healthcare professionals" (ie, health care professionals' acceptance [+ and -] and job satisfaction [+ and -]), and the "implementation process" (involvement [+] and justification and delegation [-]). All identified constructs and subconstructs of the CFIR had a high reliability rating. Some identified determinants that influence implementation may be facilitators in certain cases, whereas in others, they may be barriers. ConclusionsBarriers and facilitators were identified across all 5 CFIR domains, suggesting that the implementation process can be complex and requires implementation strategies across all CFIR domains. Stakeholders, including digital health intervention developers, health care professionals, health care organizations, health policy makers, health care funders, and researchers, can consider the identified barriers and facilitators to design tailored implementation strategies after prioritization has been carried out in their local context.